Multi-Walled Carbon Nanotubes Augment Allergic Airway Eosinophilic Inflammation by Promoting Cysteinyl Leukotriene Production - Carvalho, Sophia; Ferrini, Maria; Herritt, Lou; Holian, Andrij; Jaffar, Zeina; Roberts, Kevan (Frontiers in Pharmacology, 2018)
Multi-walled carbon nanotubes (MWCNT) have been reported to promote lung inflammation and fibrosis. The commercial demand for nanoparticle-based materials has expanded rapidly and as request for nanomaterials grows, so does the urgency of establishing an appreciation of the degree of health risk associated with their increased production and exposure. In this study, we examined whether MWCNT inhalation elicited pulmonary eosinophilic inflammation and influenced the development of allergic airway inflammatory responses. Our data revealed that instillation of FA21 MWCNT into the airways of mice resulted in a rapid increase, within 24 hours, in the number of eosinophils present in the lungs. The inflammatory response elicited was also associated with an increase in the level of cysteinyl leukotrienes (cysLTs) present in the bronchoalveolar lavage fluid. CysLTs were implicated in the airway inflammatory response since pharmacological inhibition of their biosynthesis using the 5-lipoxygenase inhibitor Zileuton resulted in a marked reduction in the severity of inflammation observed. Moreover, FA21 MWCNT entering the airways of mice suffering from house dust mite (HDM)-elicited allergic lung inflammation markedly exacerbated the intensity of the airway inflammation. This response was characterized by a pulmonary eosinophilia, lymphocyte infiltration and raised cysLT levels. The severity of pulmonary inflammation caused by either inhalation of MWCNT alone or in conjunction with HDM allergen correlated with the level of nickel present in the material, since preparations that contained higher levels of nickel (FA21, 5.54% Ni by weight) were extremely effective at eliciting or exacerbating inflammatory or allergic responses while preparations containing lower amounts of nickel (FA04, 2.54% Ni by weight) failed to initiate or exacerbate pulmonary inflammation. In summary, instillation of high nickel MWCNT into the lungs promoted eosinophilic inflammation and caused an intense exacerbation of pre-existing allergic airway inflammation by facilitating cysLT biosynthesis. These findings suggest that exposure to airborne MWCNT is likely to have adverse inflammatory effects in individuals suffering from atopic asthma and, in this context, further investigation of the therapeutic effects of pharmacological agents that block leukotriene synthesis is warranted.